Budgetary participation, locus of control, and Mexican managerial performance and job satisfaction. - Frucot, Veronique; Shearon, Winston T. (The Accounting Review, 1991)
Researchers generally agree that culture affects the behavior and attitudes of individuals within organizations (Hofstede 1980; Adler et at. 1986). Therefore, it may be assumed that an organizational system such as a participative budget-process will have different effects in different cultures. Recent research has indicated that a personality variable, internal- external locus of control, impacts the relationship between budgetary participation and both managers' performance and job satisfaction (Brownell 1981, 1982b). The locus of control construct categorizes individuals as (1) externals, those who believe that events are controlled by fate, luck, chance or powerful others, or (2) internals, those who believe that they have some control over events (Rotter 1966). This article examines whether cultural differences affect the previously identified interrelationship of individual locus of control and participation in the budgeting process as it impacts managerial performance and satisfaction. The, prior research (Brownell 1982b) used middle-level managers in US. manufacturing organizations. In this study, Mexican managers were selected because Mexico provides an interesting cultural contrast to the U.S. on three dimensions identified by Hofstede (1980) which are considered relevant to participative budgeting issues. In contrast to the Angio" Cluster, the Latin Cluster of which Mexico is a unit differs on the `dimensions `of "uncertainty avoidance" and "power distance." An additional factor in the selection of Mexican managers was the magnitude of. economic ties between Mexico and the U.S.' The importance of this. relationship continues to grow as more multinationals establish "niaqull- ladoras" within the border region and as the Mexican government frees some of its constraints on foreign investment The responses of 83 Mexican managers to survey instruments were analyzed using regression to test the interrelationship of locus of control and budgetary participation and their impact on managerial performance and job satisfaction. While the results of this study are generally consistent with previously reported findings for managerial performance, the impact of locus of control on managerial satisfaction was not significant, reflecting an ostensible difference in culture. In addition, the effect of locus of control on the performance of high-level managers was significantly stronger than its impact on the performance of lower-level managers. Finally, contrasting significantly to other Mexican managers, the performance of those Mexican managers employed in 100 percent foreign-owned firms was not discernibly affected by either budgetary participation or locus of control. This last result may be due to the cognitive dissimilarities relating to the cultural interface in these foreign-owned firms. This suggests that, within the Mexican culture, different conclusions are obtained depending on whether the firm is controlled by local or foreign interests.